2021
DOI: 10.7554/elife.65722
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying absolute gene expression profiles reveals distinct regulation of central carbon metabolism genes in yeast

Abstract: In addition to controlled expression of genes by specific regulatory circuits, the abundance of proteins and transcripts can also be influenced by physiological states of the cell such as growth rate and metabolism. Here we examine the control of gene expression by growth rate and metabolism, by analyzing a multi-omics dataset consisting of absolute-quantitative abundances of the transcriptome, proteome, and amino acids in 22 steady-state yeast cultures. We find that transcription and translation are coordinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…To generate the yeast k app dataset we collected absolute proteomics data of S. cerevisiae under diverse conditions ( 4 7 ) ( Dataset S1 ). The absolute protein abundance can be directly adopted as enzyme abundance in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…To generate the yeast k app dataset we collected absolute proteomics data of S. cerevisiae under diverse conditions ( 4 7 ) ( Dataset S1 ). The absolute protein abundance can be directly adopted as enzyme abundance in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…This could result in different cellular states that feedback globally on gene expression (Keren et al 2013). It is of note that the growthrate-dependent component defined in this study might in some cases complicate the interpretation of condition-specific responses and should then be taken into account (Pancaldi, Schubert, and Bähler 2010;Yu et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The former might involve truncations, knockouts, transcription factor engineering (see later), mRNA stability, RNA polymerase engineering, transcription factor binding sites, and direct promoter engineering. A suite of such approaches has been referred to as global transcription machinery engineering (gTME) Data are replotted from supplementary table S1a of [218]. The dilution rate from 0.1 to 0.35 h −1 is encoded by the style of symbol, and the nitrogen source by the colour indicated (optimised for colour-blind legibility via the palettes at http:// colorbrewer.org/).…”
Section: Transcription Vs Translation Engineeringmentioning
confidence: 99%
“…While transcript levels were an important contributor to this variation, the number of protein molecules per transcript in the same study also showed an impressive range, from 40 to 180 000 proteins per transcript [ 217 ], implying considerable post-transcriptional control. A more recent study in the same organism detailed absolute protein abundances under some 42 conditions [ 218 ], with data replotted therefrom in Figure 7 . This serves to show the relatively limited range available in both the total transcriptome and the total proteome in growing cell cultures.…”
Section: The Potential For Host Proteome Optimisationmentioning
confidence: 99%
See 1 more Smart Citation